Research on the dual effects of environmental protection tax law on green transformation of China’s industry - Qing Zhao; Chih-Hung Yuan (Frontiers in Environmental Science, 2025)
Based on balanced panel data from 286 prefecture-level cities across 30 provinces in China spanning 2013–2023, this study employs an intensity difference-in-differences model to systematically evaluate the promoting effect of environmental tax policies on industrial green transformation. It further investigates heterogeneous impact characteristics and underlying mechanisms. Empirical results demonstrate that the implementation of environmental tax policies significantly reduces industrial pollution emission intensity while simultaneously promoting growth in industrial value-added, achieving a “double dividend” effect of both environmental protection and economic growth. This conclusion remains robust after a series of rigorous tests and the exclusion of interference from other policies. Mechanism tests reveal that environmental tax policies primarily drive industrial green transformation through three channels: incentivizing enterprises to increase R&D investment, attracting high-quality foreign direct investment (FDI), and strengthening the efficiency of environmental tax collection and administration. Heterogeneity analysis indicates significant regional disparities in the “double dividend” effect, with it being pronounced only in the economically developed eastern region and the heavy industry-agglomerated northeastern region, while the pollution reduction effect in the central-western regions fell short of expectations. This paper provides crucial empirical evidence for refining environmental tax system design and implementing regionally differentiated environmental governance policies.